Evaluation of cassava genotypes in different harvesting times in the State of Acre, Brazil - Mendonça, Hélia Alves de; Moura, Geraldo de Melo; Cunha, Elden Teixeira (Pesquisa Agropecuaria Brasileira, 2003)
The cassava has a great economical and social importance as a basic food for the population of the State of Acre, Brazil. It is used to produce flour and it has a great potential for fresh consumption too. The aim of this work was to evaluate genotypes of cassava at different harvesting times in the State of Acre, Brazil. Ten cassava genotypes were evaluated at four harvesting times in a randomized block experimental design, arranged in a split-plot scheme with four replications, with the harvesting time in the plots and the genotypes in the subplots, during the 1999/2000 and 2000/2001 seasons. The MD-33 and Pão genotypes presented high root yield and resistance to the root rot. The MD-33 genotype is indicated for industrialization and the Pão genotype for fresh consumption. Harvesting 14 months after planting resulted in the highest root yield, but presented the highest incidence of root rot. The starch content and root rot incidence varied in the different genotypes and harvesting times evaluated.